2013
DOI: 10.1002/j.1681-4835.2013.tb00406.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Radio Frequency Identification Assimilation Process in China: A Stage‐based Model Perspective

Abstract: RFID (Radio frequency identification) is an emerging technology that attracts much attention of supply chain participants recently. However, most Chinese supply chain participants just adopt this innovation without making further steps to fully utilize its benefits. Extant IS research on this technology only focuses on factors that impact its organizational adoption. According to assimilation theory, most information technologies exhibit an "assimilation gap" which means widespread usage tends to lag behind th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…In order to address the research questions, we have slightly modified the TOE model by including the demographic characteristics of decision-makers in micro-enterprises as an important contextual factor in the current study. Despite some arguments about the limitations of the TOE model, some recent empirical studies (Balaid et al, 2014;Jie et al, 2013;Tran et al, 2014;Xin et al, 2014) have demonstrated its applicability in some parts of the developing world.…”
Section: Understanding the Contextual Factors Influencing The Adoption Of Corporate Websitesmentioning
confidence: 99%
“…In order to address the research questions, we have slightly modified the TOE model by including the demographic characteristics of decision-makers in micro-enterprises as an important contextual factor in the current study. Despite some arguments about the limitations of the TOE model, some recent empirical studies (Balaid et al, 2014;Jie et al, 2013;Tran et al, 2014;Xin et al, 2014) have demonstrated its applicability in some parts of the developing world.…”
Section: Understanding the Contextual Factors Influencing The Adoption Of Corporate Websitesmentioning
confidence: 99%